Price Support, Acreage Controls, and Efficient Redistribution - Gisser, Micha (Journal of Political Economy, 1993)
This study is concerned with the combination of target price and acreage controls as the two major mechanisms of farm policy. Acreage controls are shown to enhance the efficiency of redistribution under a target price program. More specifically, this study demonstrates that if the traditional Cobb-Douglas production function is assumed, acreage controls do not enhance the efficiency of target price programs in the process of redistributing income to the farm sector. The study proves that if the elasticity of substitution between land and all other inputs is less than one, then the income redistributional costs are likely to be reduced. Moreover, by using an empirical estimate of the elasticity of substitution and farm data for the time period 1984-88, this study demonstrates that acreage control programs have drastically reduced the deadweight losses associated with income redistribution flowing from target price programs. These results lend strong support to the public choice notion that politicians favor efficient favor efficient redistribution schemes.